2018
DOI: 10.1186/s12916-018-1077-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of neonates born following transfers of frozen-thawed cleavage-stage embryos with blastomere loss: a prospective, multicenter, cohort study

Abstract: BackgroundDespite limited information on neonatal safety, the transfer of frozen-thawed cleavage-stage embryos with blastomere loss is common in women undergoing in vitro fertilization. We aimed to evaluate the pregnancy outcomes and safety of frozen-thawed cleavage-stage embryos with blastomere loss.MethodsThis prospective, multicenter, cohort study included all frozen-thawed cleavage-stage embryo transfer (FET) cycles between 2002 and 2012. Pregnancy outcomes and subsequent neonatal outcomes were compared be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
1
10
2
Order By: Relevance
“…Details on the use of oocyte retrieval and frozenthawed embryo transfer were abstracted from the patient's hospital records as we previously described [15]. ART procedures were conducted using routine protocols, and information was documented, including the COH protocol, type of insemination, number of oocytes retrieved, the day of embryo transfer, and the number of embryos transferred.…”
Section: Data Collection and Variable Definitionmentioning
confidence: 99%
“…Details on the use of oocyte retrieval and frozenthawed embryo transfer were abstracted from the patient's hospital records as we previously described [15]. ART procedures were conducted using routine protocols, and information was documented, including the COH protocol, type of insemination, number of oocytes retrieved, the day of embryo transfer, and the number of embryos transferred.…”
Section: Data Collection and Variable Definitionmentioning
confidence: 99%
“…Pregnancy outcomes and relevant obstetric outcomes were followed up as previously described. 15 Outcomes measurements and variable specification Participants were interviewed in person to obtain information on sociodemographic characteristics and reproductive history. The height and weight were measured, and body mass index (BMI) was calculated before interview.…”
Section: Art Proceduresmentioning
confidence: 99%
“…Our previous study indicated that blastomere loss after embryo thawing could lead to a decreased pregnancy rate after embryo transfer. 21 In addition to blastomere loss, other factors, namely, embryo vitrification, open vitrification systems, and vitrification duration, have raised concern regarding their impacts on pregnancy outcomes and neonatal safety. 15,26,27 Although the long duration of cryopreservation makes it difficult to study the impact of duration on the safety of vitrification, some studies have indicated comparable pregnancy rates for FETs after short-and long-term cryopreservation and reported that birthweight in singletons is not influenced by vitrification duration.…”
Section: Discussionmentioning
confidence: 99%
“…The patient's clinical data regarding the ART procedure, including oocyte retrieval and embryo transfer, were collected from the patient's hospital records as previously described. 21 ART procedures were conducted per routine protocols, and patient information during the ART procedure, including controlled ovarian hyperstimulation (COH) protocol (gonadotropin-releasing hormone [GnRH] agonist protocol, GnRH antagonist protocol, microflare protocol or other protocol), type of insemination (IVF or ICSI), number of oocytes retrieved (≤10, 11-20 or >20), type of endometrial preparation (natural cycle, HRT cycle, or ovarian stimulation cycle), day of embryo transfer (day 3, day 4, or day 5), and number of embryos transferred (1 or 2), was documented. Endometrial thickness before embryo transfer was measured by highly trained sonographers via transvaginal ultrasound (Acuson X300, Siemens, Germany).…”
Section: Data Collection and Variable Definitionmentioning
confidence: 99%